Simbol dan Makna Berkain dalam Kalangan Pecinta Wastra - Ramadhanty, Anissa; Chandra, Nina; Ardianto, Eka; Budiman, Arief (Kajian Branding Indonesia, 2023)
Wastra is a piece of cloth that is produced in a traditional way. Wastra comes in different types, from the weaved cloth such as ulos, songket, jumputan, and batik cloth. Berkain is an activity in which an individual incorporates wastra in their day-to-day outfit. Different from how wastra was used back in the days, berkain integrates modern clothing with wastra. The purpose of this study is to understand the symbol and meaning ‘berkain’ of wastra lovers. Theories of culture, symbols, and meaning are used by the researcher as a tool to analyze the data. Qualitative research will be used with study case concepts. The data collection will be done through interview, observation, and netnography with informants. The result shows that there are similarities in culture in berkain activity that has been obtained through the ABC culture theory. The symbol that tends to be felt are Culture, Fight, and Identity. The meaning that surfaced in the berkain activity are fight and respect for the culture.